The Implementation of Pesantren Accounting at the Management of Darul Ulum Medali Islamic Boarding School in Lamongan City - Muhammad Aras Prabowo; M Ridho Malik Ibrahim; Mariska Nur Hanifah (Trescode Green Organization, 2025)
The implementation of the Accounting Guidelines for Pesantren in 2018 has greatly supported the management of Islamic boarding schools in Lamongan Regency in preparing financial reports. Pesantren is a non-profit institution that does not seek profit by increasing surpluses, receiving donations, or assistance from individuals or groups. The purpose of this study is to assess the effectiveness of implementing accounting rules for Pesantren to improve the quality, especially in the financial reports of the management of Darul Ulum Medali Islamic Boarding School. The method used in this study is a literature review taken from journals in full-text format that can be accessed, and assisted by using a descriptive approach in qualitative methods. Data is presented in descriptive format, analyzed, and conclusions drawn. Through this study, it is hoped that knowledge on how to prepare financial reports for the management of Darul Ulum Medali Islamic Boarding School in accordance with the Accounting Guidelines for Pesantren can be obtained.